(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
During the period 1981-2017, Turkish-French relations witnessed important developments, specifically during the rule of the two French presidents (François Mitterrand and Jacques Chirac), especially in the economic aspect. However, the most lukewarm years of political relations were during the era of French President (Nicolas Sarkozy) due to his repeated French statements on the issue of the reality of nationalities within Turkish society, in addition to France’s position rejecting Turkey’s accession to the European Union. It is noticed by tracing the Turkish-French diplomatic relations during the study years to the extent of the continuity of official relations between the two countries even in the presence of differences, which reflected positively on the continuation of economic and cultural relations.